Justice, development and the land: the social context of Scotland's energy transition. (19th May 2018) - Dalglish, Chris; Leslie, Alan; Brophy, Kenny; Macgregor, Gavin
Abstract: Scotland, like many other countries, is undergoing a transition to renewable energy. This paper discusses the social context within which this transition is taking place and which is conditioning the possibilities for energy development and its effects on people. In particular, the paper explores historically-rooted conflicts relating to land rights and wild land protection, considering these issues and their relationship to energy development in terms of landscape justice (i.e. the principle of fairness in the ways people relate to the landscape and to each other through the landscape). Pursuing a more just settlement between people and landscape is often a matter of understanding problematic pasts and working to overcome their harmful legacies. It is argued that there is an important role for heritage practice in helping to deliver energy development which takes the historical, social and cultural context more fully into account and thereby helps to bring about a more just settlement between people and the landscape.